Hubungan Antara Model Pembelajaran Alam Sekitar dengan Kreativitas Siswa SD Kelas Tinggi pada Pelajaran Bahasa Indonesia Materi Mengarang - Miharja, Andi Surya (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2024)
To train students' creativity, in the elementary school education unit the independent curriculum still contains various subjects, especially Indonesian language lessons. In learning Indonesian, the facts in this lesson are that most students think that learning Indonesian is difficult. Sometimes children are only taught to make sentences and read. Sometimes teachers are also confused about choosing learning materials or media because it is difficult to get them, so teachers only focus on teaching their students to read and write sentences. In high grade elementary school children (IV, V and VI), confirmation of language theories, especially writing skills, is needed. To achieve the goals of Indonesian language education, especially essay writing skills for elementary school children, especially high school students, teachers need to pay attention to the relationship between environmental learning models and student creativity and the characteristics of the students' environment around the school. The natural environment learning model is a learning model that utilizes sources from the natural environment in teaching and learning activities, which is interesting because in the natural environment students are more involved in composing the surrounding environment. with concrete objects. Elementary school age children in high class is the time when children begin to think from the concrete to the abstract. Through guidance from the teacher, children are introduced and guided to work on an essay using a natural learning model. Thus, there is a very close relationship between the environmental learning model and student creativity in Indonesian language lessons, especially in composing material for high class elementary school students (classes IV, V, and VI), starting from the teacher selecting, determining, and determining the learning model. suitable for students, to achieve learning objectives.